Increased levels of syndecan-3 are associated with childhood obesity - Diego Muñoz-Moreno; Eva Prida; Axel Y. Baumann; Raquel Pérez-Lois; Miguel Bascoy; Laura Díaz-Garzón Dopico; Beatriz Brea-García; María Villalón; Rosaura Picans-Leis; Rocío Vázquez-Cobela; Ana Estany-Gestal; Luisa María Seoane; et al. (iScience)
Summary: Childhood obesity is considered an important risk factor for developing obesity in adult. Syndecan-3 (SDC3) has recently come into focus as a possible molecular target involved in alterations of energy homeostasis, however, its role in childhood obesity remains undefined. We measured mRNA expression levels of SDC3 in children and adolescents with obesity from peripheral blood mononuclear cells and correlating them with different anthropometric and biochemical parameters. We performed a cross-sectional study involving 143 Caucasian children and adolescents. We found increased SDC3 expression in children and adolescents with obesity. In addition, a positive statistical correlation has been found between the levels of SDC3 with body weight, BMI, BMI Z score, fat mass, waist circumference, insulin levels, HOMA-IR index, and maximum blood pressure. Finally, a multiple linear regression analysis indicated that the BMI Z score variable was the most significant. Taken together, our results highlight a still unexplored link between SDC3 and childhood obesity.